The impact of bacterial and viral co‐infection in severe influenza. Issue 2 (6th April 2012) - Blyth, Christopher C.; Webb, Steve A. R.; Kok, Jen; Dwyer, Dominic E.; van Hal, Sebastiaan J.; Foo, Hong; Ginn, Andrew N.; Kesson, Alison M.; Seppelt, Ian; Iredell, Jonathan R.
<x xml:space="preserve">Abstract</x> Please cite this paper as: Blyth et al. (2013) The impact of bacterial and viral co‐infection in severe influenza. Influenza and Other Respiratory Viruses 7(2) 168–176. Background Many questions remain concerning the burden, risk factors and impact of bacterial and viral co‐infection in patients with pandemic influenza admitted to the intensive care unit (ICU). Objectives To examine the burden, risk factors and impact of bacterial and viral co‐infection in Australian patients with severe influenza. Patients/Methods A cohort study conducted in 14 ICUs was performed. Patients with proven influenza A during the 2009 influenza season were eligible for inclusion. Demographics, risk factors, clinical data, microbiological data, complications and outcomes were collected. Polymerase chain reaction for additional bacterial and viral respiratory pathogens was performed on stored respiratory samples. Results Co‐infection was identified in 23·3–26·9% of patients with severe influenza A infection: viral co‐infection, 3·2–3·4% and bacterial co‐infection, 20·5–24·7%. Staphylococcus aureus was the most frequent bacterial co‐infection followed by Streptococcus pneumoniae and Haemophilus influenzae. Patients with co‐infection were younger [mean difference in age = 8·46 years (95% CI: 0·18–16·74 years)], less likely to have significant co‐morbidities (32·0% versus 66·2%, P = 0·004) and less frequently obese [mean difference in body mass index = 6·86 (95% CI: 1·77–11·96)] compared to those without co‐infection. Conclusions Bacterial or viral co‐infection complicated one in four patients admitted to ICU with severe influenza A infection. Despite the co‐infected patients being younger and with fewer co‐morbidities, no significant difference in outcomes was observed. It is likely that co‐infection contributed to a need for ICU admission in those without other risk factors for severe influenza disease. Empiric antibiotics with staphylococcal activity should be strongly considered in all patients with severe influenza A infection.